Fitness versus Fatness and Insulin Resistance in U.S. Adolescents. (24th January 2010) - Cummings, Doyle M.; DuBose, Katrina D.; Imai, Satomi; Collier, David N.
Abstract : Background . The present study examined the relationship between insulin resistance and both waist circumference and cardiorespiratory fitness in U.S. adolescents. Methods . NHANES assessed a nationally representative sample of U.S. adolescents (12–18 yrs) between 1999–2002. Abdominal adiposity was estimated by waist circumference, overall adiposity by BMI, and cardiorespiratory fitness (maximal oxygen uptake (VO 2 max) from a treadmill exercise test). Insulin resistance was estimated from fasting insulin and glucose using the homeostatic model assessment method (i.e., HOMA) and was log-transformed. Results . 1078 adolescents were included in the study. Positive correlations existed between lnHOMA and waist circumference (r = 0.59 ;r = 0.54 ) for boys and girls, respectively. lnHOMA andVO 2 max were inversely related in boys (r = − 0.29 ) but not girls (r = − 0.06 ). Gender-specific analyses by BMI category showed that the significant inverse relationship in lnHOMA andVO 2 max was primarily present in obese boys. Conclusion . Among adolescents, important gender and BMI differences exist in the relationship between insulin resistance and fitness. While waist circumference and BMI are important predictors in all children, fitness appears especially important in obese boys. These findings may have important implications for gender-specific interventions to prevent adult obesity and diabetes mellitus.